INFORMATION TECHNOLOGIES AND COMMUNICATIONS METROLOGICAL SERVICE - Xomidov Xushnudbek Rapikjon ugli; Bakhriddinova Dilnora Sharifjon kizi; Xusanova Sarvinoz Alisher kizi (Journal of new century innovations, 2023)
Annotation: The article discusses the impact of information technology and communications on the metrology service, which is responsible for providing accurate measurements and standards for scientific and industrial purposes an.